Role of Inhaled Budesonide in Neonates with Meconium Aspiration Syndrome - Noor, Mah; Manzoor, Saima; Wamiq, Saba; Javeed, Asif (Biological and Clinical Sciences Research Journal, 2025)
Meconium aspiration syndrome (MAS) is a significant cause of neonatal morbidity and mortality, particularly in resource-limited settings like Pakistan. Inhaled corticosteroids, such as budesonide, have shown promise in reducing pulmonary inflammation and improving respiratory outcomes. This study aimed to evaluate the efficacy of inhaled budesonide compared to normal saline in reducing respiratory distress, oxygen dependency, and hospital stay among neonates with MAS. Methods: A randomized controlled trial was conducted in the Department of Pediatric Medicine, Ibn-e-Siena Hospital, Multan, Pakistan, over six months from May 2024 to October 2024. Sixty neonates (≥34 weeks' gestational age) diagnosed with MAS were randomly assigned to two groups: Group A received inhaled budesonide (50 µg in 2.5 mL normal saline via nebulization every 12 hours), while Group B received normal saline nebulization as a control. The primary outcome was the mean time to normalization of Down's score. Secondary outcomes included the duration of oxygen therapy and total length of hospital stay. Data were analyzed using SPSS version 23, with p < 0.05 considered statistically significant. Results: The mean age of neonates was 10.4 ± 3.2 hours, and 60% were male. Baseline characteristics were comparable between both groups (p > 0.05). The mean time to normalization of Down's score was significantly shorter in the budesonide group (3.54 ± 1.41 days) compared to the saline group (5.73 ± 1.48 days) (p < 0.001). Similarly, the mean duration of oxygen therapy was markedly reduced in the budesonide group (65.9 ± 28.6 hours vs. 100.8 ± 29.1 hours, p < 0.001). Hospital stay was also shorter in the budesonide group (4.33 ± 2.95 days vs. 5.77 ± 3.10 days, p = 0.02). The results remained significant across stratified analyses for gestational age, gender, and birth weight. Conclusion: Inhaled budesonide significantly improves respiratory outcomes in neonates with meconium aspiration syndrome by reducing the duration of respiratory distress, oxygen dependency, and hospital stay. Incorporating inhaled budesonide into standard MAS management protocols could enhance neonatal recovery and reduce healthcare burden, particularly in low-resource settings like Pakistan.